Clinical report of a patient with de novo trisomy 12q23.1q24.33 - (:unkn) unknown (Editions Medecine et Hygiene, 2015)
Clinical report of a patient with de novo trisomy 12q23.lq24.33: We report a patient with a rare de novo duplication of 12q23.l-12q24.33 region with a 32.7 Mb gain, having similar features seen in previously reported isolated cases of duplications of the 12q23q24 region, such as growth retardation, neuromotor retardation, corpus callosum agenesis, dysmorphic features such as, hypertelorism, epicanthus, flat nasal bridge, low-set small ears, down-turned comers of the mouth, micrognathia, cryptorchidism and limb anomalies such as pes piano valgus, prominent heels and overriding toes. Our patient has Noonan-like features, such as short stature, short neck, epicanthal folds, ptosis of eyelids, hypertelorism, pectus excavatum, widely spaced nipples and cryptorchidism. Duplication of PTPN11 gene has been postulated as a mechanism for the Noonan syndrome. Phenotypic features and the genes involved in this region are important to further delineate the 12q23q24 phenotype.
Keywords: Duplication of 12q23q24; PTPN11 gene; Trisomy 12q23.1-12q24.33